SMEs’ Sustainability in Kailali and Kanchanpur District of Nepal - Bhandari, Avishek; Kunwar, Nrip Bahandur; Kandel, Puja (Nepalese Journal of Management Science and Research, 2026)
In peripheral border regions, Small and Medium Enterprises (SMEs) are an important source for employment creation, income generation and local economic development in Nepal. The present study analyses the factors which determine the sustainability of SMEs in the two districts,Kailali and Kanchanpur, of the Sudurpaschim Province, using a quantitative research approach. Primary data were gathered by means of a standardized questionnaire from 550 registered SMEs engaged in trade, manufacturing and services. Descriptive statistics as well as a multiple regression analysis were applied to investigate the effects of access to finance, managerial capabilities, market access, infrastructural conditions and support of the government on business sustainability. As a result, it was found out that the access to finance, managerial capabilities and the access to markets have significant positive effects on the sustainability of SMEs. In contrast, the poor quality of the infrastructure and the low effectiveness of the government’s support represent major barriers to sustainable entrepreneurship in border districts. The findings emphasize the necessity of a combination of financial and digital literacy programs for SMEs and better access to adequate financial services, as well as targeted capacity-building activities designed specifically for the needs of SMEs located in peripheral border regions. Finally, the study concludes that to improve the long-term sustainability of SMEs in peripheral border regions of Nepal, governmental policies need to be developed that at the same time, aim to develop the human capital and eliminate structural limitations within the financial sector.